PENERAPAN METODE ABA (APPLIED BEHAVIOR ANALYSIS) DALAM MENINGKATKAN KEMAMPUAN PERILAKU, INTERKASI SOSIAL, BAHASA DAN KOMUNIKASI ANAK AUTIS - Hildawati (Paedagogia: Jurnal Pendidikan, 2018)
Method in improving behavioral abilities, social interactions, communication and language of autistic children in Taman Pelatihan Harapan Makassar. This type of research is qualitative descriptive which is factually and systematically describes the description of the ABA method (Applied Behavior -Analysis applied to the learning process of autistic children in Taman Pelatihan Harapan).The study uses psychological, sociological, and pedagogical approach. The source of data in this study is the therapist of the Taman Pelatihan Makassar, and parents of autistic children. The results of the study show that the ABA method is a method applied to autistic children through behavioral habituation that can increase the personality capacity of autistic children, especially ability in behavior, social interaction, communication and language. This is caused by several supporting factors such as therapists who master the application of the ABA method, the infrastructure that supports it, and good collaboration between parents and therapists.